Young digital citizen answers: Can online learning improve the quality of civic education learning? - Halimi, Muhammad; Rahmat, Rahmat; Nugraha, Restu Adi; Pratiwi, Elda Dwi (Jurnal Civics: Media Kajian Kewarganegaraan, 2022)
Technological developments have an impact on various fields, in education particularly, the 21st-century learning requires lectures and learners to be creative and innovative in utilizing digital media effectively, by using the right methods, the learning process in the digital era will be carried out optimally, to improve the quality of learning by learning objectives. This research used a mixed design approach with a survey as its main method. The participants of this study were lecturers and students of the PKn UPI Study Program using online learning in an online learning system (SPADA UPI) and Integrated Online Learning System (SPOT UPI) at Universitas Pendidikan Indonesia. The results show that online learning can improve the quality of Civics learning if technology can be integrated into the Civics learning curriculum, lectures who can use digital media and digital literacy, and teaching materials that can develop 21st-century civic competencies to prepare young citizens in facing the era of disruption. Students as young citizens can be directed to master digital citizenship skills so that they can become citizens who have democratic, wise, and responsible competencies in the digital era.